Step-by-step explanation:
multiplying expressions.
remember every term of one expression has to be multiplied with every term of the other expression, and the results are added up (while considering their individual signs, of course).
1.
(-3×3 + 2x - 4)(3x - 2)
(-9 + 2x - 4)(3x - 2)
(-13 + 2x)(3x - 2) = -13×3x + -13×-2 + 2x×3x + 2x×-2 =
= -39x + 26 + 6x² - 4x = 6x² - 43x + 26
2.
let's do the other multiplication and compare the result with the result of 1 :
(-13 + 2x)(2x - 3) = -13×2x + -13×-3 + 2x×2x + 2x×-3 =
= -26x + 39 + 4x² - 6x = 4x² - 32x + 39
no, this product is not the same as in 1.
Answer: A is first
Step-by-step explanation:
Lets look at the info we have:-
Ashley found 78 rocks on Monday.
Devin found 45 rocks on Tuesday.
Question:-
How many did they find both days?
The key word for this is "both". So we need to add here. Lets add:-
78 + 45 = 123
So, Ashley and Devin together found 123 rocks.
Hope I helped ya!! xD
W + 2w = 60
this equation is wrong
Answer: 89 x 87 =7,743
Step-by-step explanation: